From Assessing to Conserving Biodiversity Conceptual and Practical Challenges - Casetta, Elena; Marques da Silva, Jorge; Vecchi, Davide (History, Philosophy and Theory of the Life Sciences, 2019)
This open access book features essays written by philosophers, biologists, ecologists and conservation scientists facing the current biodiversity crisis. Despite increasing communication, accelerating policy and management responses, and notwithstanding improving ecosystem assessment and endangered species knowledge, conserving biodiversity continues to be more a concern than an accomplished task. Why is it so? The overexploitation of natural resources by our species is a frequently recognised factor, while the short-term economic interests of governments and stakeholders typically clash with the burdens that implementing conservation actions imply. But this is not the whole story. This book develops a different perspective on the problem by exploring the conceptual challenges and practical defiance posed by conserving biodiversity, namely: on the one hand, the difficulties in defining what biodiversity is and characterizing that "thing" to which the word 'biodiversity' refers to; on the other hand, the reasons why assessing biodiversity and putting in place effective conservation actions is arduous. ; Features essays that are explicitly critical of the species approach to biodiversity Presents bio-philosophical perspectives on the interaction between biodiversity's units, levels, and scales Serves as an interdisciplinary contribution to the emergent field of biodiversity studies